Pre‐existing humoral immune comebacks control the development of the severe form of coronavirus disease 2019 in Gaucher patients - Manoj Kumar Pandey (Wiley, 2022)
Abstract Coronavirus disease 2019 (COVID‐19) and the Gaucher disease (GD) exhibit lot of resemblances in induction of innate and adaptive immune inflammation that include the immune cells activation and the massive generation of pro‐inflammatory cytokines, chemokines, and growth factors, which are all critical for propagation of the disease process and the multiple organ damage. However, majority of the GD patients have not revealed the expansion of severe form of the COVID‐19. This study suggests that the pre‐existing humoral immunity influence the devlopment of strong network of antibodies to different structural proteins of SARS‐CoV2 in GD patients with COVID‐19. Such antibodies and virus proteins interaction cause the comprehensive neutralization of SARS‐CoV2 and provides protection from the development of severe form of COVID‐19 in GD patients. This information could be helpful for better understanding of the disease mechanism as well as the development of additional potential therapy that could stop the growth of the severe symptoms and/or death in GD patients with COVID‐19.